Fenomena Judi Online yang Semakin Meluas dan Dampaknya terhadap Mahasiswa Serta Kesehatan Mental - Catharina Jean Sinaga (Lembaga Pengembangan Kinerja Dosen, 2026)
Online gambling is a form of addictive behavior that often begins with simple experimentation. Early wins tend to encourage individuals to continue gambling with increasingly larger stakes, driven by the belief that higher bets will lead to greater profits. Along with the rapid advancement of digital technology, online gambling has become more accessible to various groups, including university students, through convenient and flexible online platforms. Although it is often perceived as a form of entertainment, online gambling has significant negative impacts. This study aims to analyze the effects of online gambling on students’ mental health. The research uses a qualitative approach, with data collected through observations and interviews involving respondents who engage in online gambling activities. The findings reveal that online gambling has detrimental effects on students’ psychological well-being, including increased levels of stress, anxiety, depression, and sleep disturbances. Furthermore, it contributes to decreased concentration, reduced learning motivation, and declining academic performance. Therefore, stronger preventive measures and educational efforts are necessary to minimize the negative impacts of online gambling among university students.